Physical Quality of Tomato Powder (Lycopersicum Esculentum Mill.) Produced by Foam-Mat Drying Method Using Convection Oven - Dian Purbasari; Gerry Ardhyansyah (The University of Lampung, 2024)
Tomatoes (Lycopersicum esculentumMill.) have a fairly low shelf life, therefore further processing is needed to increase the shelf life and economic value of tomatoes, one of which is by processing it into tomato powder. The purpose of this study was to determine the physical quality of tomato powder produced from foam drying in a convection oven at different temperature variations and concentrations of Tween 80. This research method used a completely randomized design with two treatment variables, namely temperature and concentration of foaming agent Tween 80. The temperatures used were 60, 70, and 80°C while the concentration of Tween 80 used was 0.4; 0.7; and 1.0%. Data analysis used a two-way ANOVA test followed by the Duncan test and correlation test. The physical quality parameters of tomato powder showed values of the fineness modulus ranging from 1.19 – 1.77; the grain size value ranges from 0.0094 – 0.0141 mm; powder moisture content values range from 5.36 – 6.48%bb; L values range from 76.20 – 79.01; a value ranges from 12.51 – 14.81; b values range from 18.21 – 21.73; bulk density values range from 0.56 – 0.63 g/cm3; oil absorption value ranges from 0.85 – 0.89 ml/g; angle of repose values range from 33.65 – 36.09°. The temperature difference affects the fineness modulus, grain size, and moisture content. While the difference in the concentration of Tween 80 affects the color parameters (L, a, b), bulk density, and angle of repose. Keywords: Drying, Foaming agent, Physical Quality, Temperature, Tomatoes.